Recent Uses of Photogenerated Oxygen-Centered Radicals in Intermolecular C–O Bond Formation - Banoun, Camille; Magnier, Emmanuel; Dagousset, Guillaume (Synlett, 2023)
We report herein recent advances made by our group and others in the field of oxygen-centered radicals generated under photocatalysis. Thanks to the design of new O-radical precursors, these radicals can now be efficiently trapped by unsaturated systems in an intermolecular manner, via the formation of a new C–O bond.1 Introduction2 Reactions Involving Carbonyloxy Radicals3 Reactions Involving Fluoroalkoxy Radicals4 Reactions Involving Alkoxy Radicals5 Conclusion
Keywords: radicals; carbonyloxy; fluoroalkoxy; alkoxy; photoredox catalysis; C–O bonds